Treatment of Waste Extract Lubricating Oil by Thermal Cracking Process to Produce Light Fractions - Kadhim Idan, Fatimah; Mohammed Obyed, Saleem (Iraqi Journal of Chemical and Petroleum Engineering, 2018)
This work deals with thermal cracking of three samples of extract lubricating oil produced as a by-product from furfural extraction process of lubricating oil base stock in AL-Dura refinery. The thermal cracking processes were carried out at a temperature range of 325-400 ºC and atmospheric pressure by batch laboratory reactor. The distillation of cracking liquid products was achieved by general ASTM distillation (ASTM D -86) for separation of gasoline fraction up to 220 ºC from light cycle oil fraction above 220 ºC. The comparison between the conversions at different operating conditions of thermal cracking processes indicates that a high conversion was obtained at 375°C, according to gasoline production. According to gasoline production, noticed that sample (3) was the best due to their high gasoline product at thermal cracking, so another distillation will occur to obtain other composition and its volume present. Gasoline and kerosene conversion was 19 % and for light cycle oil 81% for the best one (sample 3).